Recomendaciones para mejorar la operatividad de la carga de comercio exterior en la Sociedad Portuaria Regional de Buenaventura (2015)
The present deepening work begins with a description of the main operations or subsystems in which the port facility is formed. Subsequently, it describes the main indicators of port performance and efficiency proposed by UNCTAD, ECLAC, the World Bank, Nathan Associates Inc., the Superintendence of Ports and Transport and those that are currently contained in the contract of the port concession of the Port Society Regional of Buenaventura hereinafter SPRBUN. Below we identify some ports with conditions similar to the SPRBUN in order to carry out a comparative analysis of the indicators to be proposed. Finally, the most representative variables that affect the port capacity are identified, from which performance indicators are formulated for the main port operations that are carried out in the facilities of the Regional Port Authority of Buenaventura and recommendations are proposed. that seek to improve the general conditions of operation, establish operational requirements, regulations and policies, along with control and supervision proposals that contribute to the reduction of time, additionally proposing works and infrastructure improvements that contribute to the reduction of time in the logistics chain .